PERANCANGAN SISTEM INFORMASI VERIFIKASI DANA HIBAH MENGGUNAKAN PHP MYSQL PADA BIRO PELAYANAN SOSIAL DASAR BAGIAN AGAMA DI SETDA PROVINSI JAWA BARAT - Dwi Robiul; Wina Lupi Siti Lutpiah (INFOKOM (Informatika & Komputer), 2021)
Abstract At this time, where the development of technology and information developed quickly. This has an impact on the ease in various field of work, including the field of grant verification. The use of computer technology makes the grant verification process more effective and efficient. The bureau of basic sosial service in the religious section is one of the institution in the local government system, occupying an important and strategic sequence in relation to the implementation of regional development, especially in the field of religion. In the grant verification system that runs, there are still some obstacles both in the data recording that is still using Microsoft Excel and also Microsoft Word and its data storage, so it is possible mistakes happen in recording and searching data. Based on this background of the problem, the author are encourage to create a grant verification program that is expected to help the process of grant verification become more effective and efficient. The grant verification program is created using PHP and with MySql database. The use of a grant verification program to be the right solution to simplify the process of input institutions data and input verification agencies data, easy in searching data and reports produced will be more accurate. Keywords : Information System Design, PHP, MySql